2019
DOI: 10.1051/epjap/2018180282
|View full text |Cite
|
Sign up to set email alerts
|

Measure and analysis of 4H-SiC Schottky barrier height with Mo contacts

Abstract: Current–voltage (I–V) and capacitance–voltage (C–V) characteristics of Schottky Mo/4H-SiC diodes have been measured and analyzed as a function of temperature between 80 and 400 K. The I–V characteristics significantly deviate from ideal characteristics predicted by the thermionic emission model because of the inhomogeneity of Schottky contact. After a brief review of the different existing models, the main parameters (ideality factor, barrier height, and effective Richardson constant) of both diodes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…q is the charge of electron, V is the applied voltage, A is the device area, k is the Boltzmann's constant, T is absolute temperature, A* is the effective Richardson constant, n is the ideality factor and ϕ b is the barrier potential and IS is the saturation current [21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…q is the charge of electron, V is the applied voltage, A is the device area, k is the Boltzmann's constant, T is absolute temperature, A* is the effective Richardson constant, n is the ideality factor and ϕ b is the barrier potential and IS is the saturation current [21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Modeling the inhomogeneous Schottky interface usually assumes the presence of multiple tiny zones (patches) with different barrier heights on the contact surface, which contribute variably to the total current according to the thermionic emission transport mechanism [1]- [19]. This parallel conduction theory is, thus, the cornerstone of all current non-uniformity models [3]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…This parallel conduction theory is, thus, the cornerstone of all current non-uniformity models [3]- [13]. The most prominent assumes a Gaussian distribution of patches on a Schottky contact's surface [1], [5], [6], [12], [14]. While this approach was proven adequate for modeling devices over limited temperature ranges, it was quickly demonstrated that, at cryogenic temperatures, it is "in significant error" [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical considerations of the exact conduction mechanisms in the ON-state and the OFF-state have also been widely investigated, with Tung's description of thermionic field emission dominating the conduction of Schottky diodes being the basis of most attempts to exactly model both leakage current levels and ON-state performance [10], [11]. Over the past decade, industrial suppliers have moved away from high work function metals such as nickel (Ni) toward lower work function metals such as titanium (Ti) [12], [13] and molybdenum [14], [15], where a decrease in forward voltage drop has come at the expense of higher leakage currents. More recently, molybdenum nitride (MoN) has been selected as metal by companies for their low barrier height devices [16], [17], which were demonstrated to have even lower barrier heights.…”
mentioning
confidence: 99%